No additional benefit of prescribing a very low-protein diet in patients with advanced chronic kidney disease under regular nephrology care: a pragmatic, randomized, controlled trial. Issue 5 (30th December 2021) - Bellizzi, Vincenzo; Signoriello, Simona; Minutolo, Roberto; Di Iorio, Biagio; Nazzaro, Paola; Garofalo, Carlo; Calella, Patrizia; Chiodini, Paolo; De Nicola, Luca; ,
ABSTRACT: Background: Whether a very low-protein diet supplemented with ketoanalogues (sVLPD), compared with a standard low-protein diet (LPD), improves outcomes in patients with chronic kidney disease (CKD) under stable nephrology care is undefined. Objectives: To compare the effectiveness of sVLPD compared with LPD in patients regularly seen in tertiary nephrology care. Methods: Participants were patients with CKD stages 4–5, followed for at least 6 mo, randomly allocated to receive sVLPD or LPD [0.35 or 0.60 g/kg ideal body weight (IBW)/d, respectively], stratified by center and CKD stage. The primary outcome was time to renal death, defined as the first event between end-stage renal disease (ESRD) and all-cause mortality; secondary outcomes were the single components of the primary outcome, cardiovascular outcome, and nutritional status. Results: We analyzed 223 patients (sVLPD, n  = 107; LPD, n  = 116). Mean age was 64 y, 61% were male, and 35% had diabetes. Median protein intake (PI), which was 0.8 g/kg IBW/d at baseline in both groups, was 0.83 and 0.60 g/kg IBW/d in LPD and sVLPD, respectively, during the trial with a large decrease only in sVLPD ( P = 0.011). During a median of 74.2 mo, we recorded 180 renal deaths (141 dialysis and 39 deaths before dialysis). Risk of renal death did not differ in sVLPD compared with LPD (HR: 1.17; 95% CI: 0.88, 1.57; P = 0.28). No difference was observed for ESRD (HR: 1.12; 95% CI: 0.81, 1.56; P = 0.51), mortality (HR: 0.95; 95% CI: 0.62, 1.45; P = 0.82), or time to fatal/nonfatal cardiovascular events ( P  = 0.2, log-rank test). After 36 mo, still active patients were 45 in sVLPD and 56 in LPD. No change of nutritional status emerged during the study in any arm. Conclusions: This long-term pragmatic trial found that in patients with CKD under stable nephrology care, adherence to protein restriction is low. Prescribing sVLPD compared with standard LPD is safe but does not provide additional advantage to the kidney or patient survival. Graphical Abstract: